Influence of shot peening and hard chromium electroplating on the fatigue strength of 7050-T7451 aluminum alloy - Carvalho, A. L. M.; Voorwald, H. J. C. (Elsevier B.V., 2007)
Chromium electrodeposition is a technique for the production of functional coatings on engineering components. These coatings are extensively micro-cracked and present high level of hardness, resistance to corrosion and wear and low coefficient of friction. In this paper the shot peening influence on the fatigue strength of aluminum 7050-T7451 alloy chromium electroplated, was investigated.The shot peening process was carried out to create residual stresses using ceramic and glass shots. A hard chromium electroplated coating of 100 mu m thickness was performed on the base material and the shot peened base material surfaces. S-N curves were obtained in axial and bending fatigue tests and compared with the 7050-T7451 aluminum alloy. In order to study the influence of residual stresses on fatigue life, the behavior of compressive residual stress field was measured by an X-ray tensometry.An increase in the axial fatigue strength of 25% and 50% of ceramic and glass shots, respectively, was observed. The lower performance in fatigue life for ceramic-shot peening may be attributed to higher surface damage, as a consequence of the overpeening intensity performed. However, in bending fatigue the behavior was practically equivalent for both processes. Fracture surface analysis by scanning electron microscopy was used to observe crack origin sites from shot peened and chromium electroplated samples. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: fatigue; shot peening; residual stress; hard chromium electroplating; aluminum alloy